The Role of Citizens Education in forming the Attitude of Diversity Tolerance - Arifin Arifin (Jurnal Mantik, 2019)
The attitude of tolerance develops within the framework of the existence of diversity in various dimensions of people's lives, so that harmony and harmony in life can be realized, far from conflict and social tension, especially conflicts and hostility between fellow communities. This study aims to describe the importance of the role of civic education in forming an attitude of tolerance towards diversity with a pluralistic society background. This plurality often occurs within the scope of the school, where students learn to respect and appreciate differences and accept each other for certain characteristics that may not be encountered in their environment. The method used in this study is a qualitative descriptive method, which is to describe the role of civics education in forming an attitude of tolerance while understanding phenomena, events and thoughts from individuals or groups, the results of this study explain that civic education can build tolerance among students, plays a very important role and it is proven as we know that tolerance is an absolute requirement for practicing Pancasila and mutual respect between diversity.